Exploring the Perception of Parents on the Participation of Learners with Special Educational Needs in a Virtual Talent Show - Mohamad, Suhaila (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2023)
There is a paucity of research that focuses on understanding the perception of parents in supporting the talent development of their children with Special Educational Needs (SEN). Considering the gap in the literature, participants in this study are purposely sampled from the parents whose children with SEN participated in a virtual talent show (VTS) organised by National Association of Special Education, Malaysia (NASE) during the pandemic lockdown. A total of six parents responded to the survey questionnaires and participated in the semi-structured interviews which were transcribed verbatim. The thematic data analysis revealed three categories: 1)Parents as partners, 2)Roles of NGOs and 3)Resources. This study contributes to the literature from parents’ perception on how they provided exposure in VTS that impacts the development of their children. The findings also provide new insight into what drives the parents into enrolling their children in VTS and revealed how parents agreed that participation in VTS provided positive impact and progress for their children. In addition, the result from this study highlights the positive perception of parents regarding the participation of learners with SEN in VTS. It underscores the importance of NGOs in providing opportunities for their children’s involvement and emphasises the need to address the barriers and challenges that exist. Additionally, the study demonstrates that parents strongly desire more NGOs to offer opportunities for their children with SEN to be involved in talent show performances. Despite the barriers and challenges faced, parents recognise the value and potential impact of such experiences on their children’s overall development. The findings contribute to the existing knowledge and call for further research to promote inclusivity and support the talent development of learners with SEN. It also demonstrated that parents want more NGOs to provide the opportunity for their learners with SEN to be involved in more talent shows performances, despite the barriers and challenges that arise. Future study could explore strategies to address the identified barriers and challenges and evaluate the long-term effects of participation on the well-being and self-esteem of learners with SEN. The suggestions for future studies aim to inform the development of more inclusive practices and policies that support the talent development and empowerment of learners with SEN in talent show settings.